Power to the people ? - Sivaramakrishnan, K .C (New Delhi, 2000)
The book identifies the pending issues in the functional and financial domain of the local bodies, the ambivalence and contradictions in the state laws and their implementation, the conflicts emerging already between different levels of elected leadership and how state control continues to hinder progress.
Keywords: Decentralisation